PERAN MODEL VARK (VISUAL, AUDITORI, READ WRITE, KINESTETIK) DALAM MENINGKATKAN KUALITAS KEGIATAN BELAJAR MENGAJAR (KBM) DI SMA NEGERI 5 KOTA SUKABUMI - Andika Gumelar; Siti Qomariyah; Rhama Dian Putra; Hoerul Anwar; Herdi (STKIP Subang, 2026)
This study aims to determine the role of the VARK learning model (Visual, Auditory, Read/Write, Kinesthetic) in improving the quality of Teaching and Learning Activities at SMAN 5 Sukabumi City. The VARK learning model is a learning approach that adjusts the learning process to students' learning styles, namely visual, auditory, read/write, and kinesthetic. The implementation of this model is expected to create a more effective, active, and enjoyable learning process. This study used a qualitative approach with a descriptive method. The research subjects consisted of three informants, namely the principal, a subject teacher, and one student. Data collection techniques were carried out through observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results of the study showed that the VARK learning model has a positive role in improving the quality of teaching and learning activities at SMAN 5 Sukabumi City. This can be seen from the increase in student participation during learning, good interaction between teachers and students, the use of varied learning methods, improved student understanding of the material, increased learning motivation, and the creation of a more conducive and enjoyable classroom atmosphere. Based on observations in Class X.A consisting of 40 students, it was found that students had diverse learning styles: 14 visual students, 9 auditory students, 7 read/write students, and 10 kinesthetic students. This condition indicates that the VARK model is suitable to be applied because it is able to accommodate students’ diverse learning needs. Thus, it can be concluded that the VARK learning model plays an important role in improving the quality of teaching and learning activities at SMAN 5 Sukabumi City.